Reduced auxin signalling through the cyclophilin gene DIAGEOTROPICA impacts tomato fruit development and metabolism during ripening - Batista-Silva, Willian (Journal of experimental botany, 2022)
© The Author(s) 2022. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.